2007
DOI: 10.1007/s10681-007-9486-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of yield, quality and shelf life characteristics in tomato under normal and late planting conditions

Abstract: Seventy nine genotypes of tomato (15 lines, four testers and their 60 F 1 hybrids produced in line · tester fashion) were evaluated under normal (E 1 ) and late planting (E 2 ) conditions in the Department of Vegetable Crops, Punjab Agricultural University, Ludhiana, India, to determine the nature of gene action controlling yield, quality and shelf life characteristics and to identify a few good combiner genotypes which may be used in further breeding programmes to extend the fruit availability period of tomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
25
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 17 publications
7
25
0
2
Order By: Relevance
“…This indicated that these genetic parameters are unstable with different environmental conditions. Similar results were obtained by Garg et al, (2008), Adalid et al, (2012 and El-Nagashy (2012). CONCLUSION In conclusion, due to the pervious results, which confirmed the role of both additive and non-additive genetic variances in the inheritance of studied traits with different levels, the suggested suitable breeding program for improving these traits is recurrent selection program for vegetative traits and production of hybrids for fruit characters and chemical traits.…”
Section: (2010) and Singh Et Al (2011)supporting
confidence: 89%
“…This indicated that these genetic parameters are unstable with different environmental conditions. Similar results were obtained by Garg et al, (2008), Adalid et al, (2012 and El-Nagashy (2012). CONCLUSION In conclusion, due to the pervious results, which confirmed the role of both additive and non-additive genetic variances in the inheritance of studied traits with different levels, the suggested suitable breeding program for improving these traits is recurrent selection program for vegetative traits and production of hybrids for fruit characters and chemical traits.…”
Section: (2010) and Singh Et Al (2011)supporting
confidence: 89%
“…The estimates of the quadratic component of sˆi j of all traits were relatively higher than those of gˆi (Table 2) and the interpopulational breeding strategies are the most recommended for the improvement of these variables (Amaral Júnior et al 1999, Garg et al 2008, Shende et al 2012, Souza et al 2012, Saleem et al 2013). …”
Section: Resultsmentioning
confidence: 99%
“…The following fruit traits were evaluated: weight (W; g), diameter (D; cm), height (H; cm), shape (Sh; height/diameter), and shelf life (SL; in days from harvest to fruit softening or excessive wrinkling), following the methodology proposed by Garg et al (2008). In addition, the soluble solids content (SS, °Brix), measured with a hand refractometer, pH, titratable acidity of the homogenized juice (TA, g), pericarp thickness (PT, mm), locule number (LN), and fruit firmness (F), on the equatorial plane in two opposite areas of the fruit measured with a durometer type Shore A (Durofel DFT100, 0.10 cm 2 ) were assessed.…”
Section: Phenotypic Analysismentioning
confidence: 99%